1992
DOI: 10.1099/0022-1317-73-10-2631
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of DNA Supercoiling on Transcription of Adenovirus Genes in vitro

Abstract: We examined the effect of DNA template topology on the transcription of immediate early (E 1 a), early (E 1 b) and late (pIX) adenovirus genes in vitro. Transcription in whole cell extracts was measured by quantitative hybridization to end-labelled DNA and protection of hybrids from $1 nuclease digestion. Two-to fourfold more E la RNA was synthesized from supercoiled, compared to linear, DNA templates. Similarly, transcription of the Elb gene was stimulated three-to sevenfold when the template was supercoiled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
1
6
1
Order By: Relevance
“…We found that most partially hybridized RNAs were associated with CCC mtDNA (structure e ); given that highly supercoiled DNA plasmids are better transcriptional templates in bacteria (47) and adenovirus (56), our results are consistent with CCC mtDNA being a major template for transcription in vivo . This idea is supported by observations of promoter-specific transcription on supercoiled templates using yeast mitochondrial RNA polymerase (POLRMT) in vitro (57), although mammalian POLRMT does not show promoter specificity (58).…”
Section: Discussionsupporting
confidence: 78%
“…We found that most partially hybridized RNAs were associated with CCC mtDNA (structure e ); given that highly supercoiled DNA plasmids are better transcriptional templates in bacteria (47) and adenovirus (56), our results are consistent with CCC mtDNA being a major template for transcription in vivo . This idea is supported by observations of promoter-specific transcription on supercoiled templates using yeast mitochondrial RNA polymerase (POLRMT) in vitro (57), although mammalian POLRMT does not show promoter specificity (58).…”
Section: Discussionsupporting
confidence: 78%
“…Topoisomerase I1 has been proposed to have both catalytic (chromatin loop fastener) and structural (scaffold) roles in chromosome condensation (Adachi et al, 1989). We observed that topoisomerase 11-mediated DNA catenation (Cantor et al, 1988;Banerjee and Spector, 1992) and RNA pol 11-dependent transcription (S. Banerjee, unpublished data) in HIE dialysed in the presence of 10-12 mM Mg++ were much higher than that seen in Mg++-free extracts described in this work. Preincubation of HIE in the absence of Mg++ might have further inhibited these activities.…”
Section: Discussionmentioning
confidence: 49%
“…In the case of adenoviruses, the superhelicity was suggested to facilitate unwinding of DNA during transcription (25). Similarly, the negative superhelicity of the linear replicons in Streptomyces may also be important for transcription, or alternatively replication, packaging or other DNA transaction activities.…”
Section: Discussionmentioning
confidence: 99%
“…The TP–TP interactions allow these linear replicons to assume more compact superhelical structures. The superhelicity increases transcription of adenoviral genes in a promoter-specific manner (25). …”
Section: Introductionmentioning
confidence: 99%